2005
DOI: 10.1139/l05-020
|View full text |Cite
|
Sign up to set email alerts
|

Field measurements of ice-jam-release surges

Abstract: Surges are the most violent and spectacular events that occur during the ice breakup. Upon the release of an ice jam, water and ice held by the jam are suddenly free to move. The resulting surge generates increased water stages and higher flow velocities, such that the water wave and ice run pose a risk to downstream structures, people, and aquatic life. Climate-induced changes to river ice processes, such as enhanced mid-winter jamming or increased spring flows, could result in more frequent occurrence of maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…As mentioned earlier, ice-jam releases generate steep waves of considerable height (Beltaos and Burrell 2005a). Wavegenerated velocities and bed shear stresses can be much greater that those experienced during open-water floods, especially in wide and steep rivers at high flow (Beltaos 1995;Beltaos and Burrell 2005b).…”
Section: Scour Potential Of Ice-jam Release Wavesmentioning
confidence: 96%
“…As mentioned earlier, ice-jam releases generate steep waves of considerable height (Beltaos and Burrell 2005a). Wavegenerated velocities and bed shear stresses can be much greater that those experienced during open-water floods, especially in wide and steep rivers at high flow (Beltaos 1995;Beltaos and Burrell 2005b).…”
Section: Scour Potential Of Ice-jam Release Wavesmentioning
confidence: 96%
“…Based on field measurements, Beltaos and Burrell (2005, 2010 analyzed the variation process of water temperature and water level during the period of river breakup. It is shown that flow heat transfer rate was influenced by the maximum roughness and porosity of ice jams during the breakup periods.…”
Section: Introductionmentioning
confidence: 99%
“…In the past 30 years much research has led to increased knowledge of ice jams and associated river hydraulics. Studies have documented changes in break up timing during spring (Prowse & Bonsal, 2004), characteristics of ice jam release surges (Jasek, 2003;Beltaos & Burrell, 2005) and the impacts of climate variability on ice jam events (Beltaos, 2002;Prowse & Conly, 1998;Prowse & Beltaos, 2002). The confluence of rivers is a location where ice jams often form.…”
Section: Introductionmentioning
confidence: 99%